Synthesis and Structural Studies of First Row Transition Metal Complexes with Tetradentate ONNO Donor Schiff Base Derived from 5-Acetyl 2,4-dihydroxyacetophenone and Ethylenediamine - Pulimamidi Saritha Reddy; P. V. Ananthalakshmi; V. Jayatyagaraju (E-Journal of Chemistry)
Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II) and Zn(II) complexes were prepared by template reaction of 5-acetyl 2,4-dihydroxyacetophenone (H2-ADA) and ethylenediamine in the presence of metal ions. The complexes have been characterized on the basis of elemental analyses, conductivity, magnetic moments, infrared and electronic spectral data. The Schiff base binds to metal ions in bis-multidentate ONNO mode leading to two dimensional Schiff base polymers. All the complexes have been assigned octahedral stereochemistry.